Pengaruh Tingkat Pengetahuan Perpajakan, Sikap Wajib Pajak dan Tarif Pajak Terhadap Kepatuhan Membayar Pajak (Studi Kasus Pada UMKM di Kabupaten Buleleng) - Kadek Disi Dianartini; I Putu Gede Diatmika (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
In order to achieve the predetermined tax target, one of the obstacles is the low obedient or obedient behavior shown by the taxpayer, so this condition has an impact on the realization of tax revenue. This research has a purpose to understand how the impact given by the level of tax knowledge, taxpayer attitudes, and tax rates on tax compliance. Researchers determine the selection of research objects in Micro, Small and Medium Enterprises in Buleleng Regency. Quantitative as a rule used in this research by selecting primary data as the root of data acquisition through questionnaires intermediate. In this research, the population used is all those who are classified as individual taxpayers and micro and small business owners in Buleleng Regency, Bali who have been registered at the Singaraja Pratama Tax Office with data in 2019 amounting to 6,120. Based on the population size by choosing the Slovin formula, it is known that the number of samples is 99 respondents. The way to collect data is to distribute it online through an intermediary google form as an action to prevent the spread of covid 19. The way of analyzing data uses the assistance of the SPSS version 20 for Windows program. The results of this research provide evidence that tax knowledge (X1) contributes positively and significantly to tax compliance with sig. is worth 0.004 <0.05. Then the attitude of the taxpayer (X2) contributes positively and significantly to tax compliance with sig. is worth 0,000. Furthermore, the tax rate (X3) has a positive and significant effect on tax compliance with sig. 0.003 <0.05.